Information seeking behaviour / Ahmad Aidil Rafiq Kamal, Nooranisah Ahmad and Nurfatin Safura Jamaluddin - Kamal, Ahmad Aidil Rafiq; Ahmad, Nooranisah; Jamaluddin, Nurfatin Safura (Faculty of Information Management, 2015)
This article shows an abstract of information looking for behaviour which consists of the definition of information seeking behaviour, the need for data, the tool used to search for information, a multidisciplinary prospective of research, and the problem faces when searching for data. The purpose of this article is simply to present the importance of information seeking behaviour among students, lectures, and researchers and after that they can discover of how the theme can refer one to another and, perhaps, propose the new political theory into a more general framework. It demonstrates that the survey of information seeking behaviour is right away a well-defined field of inquiry within an information acquisition.